Differentiation of Human‐Induced Pluripotent Stem Cells to Macrophages for Disease Modeling and Functional Genomics. (10th December 2018) - Shi, Jianting; Xue, Chenyi; Liu, Wen; Zhang, Hanrui
Abstract: Macrophages play important roles in many diseases. We describe a protocol and the associated resources for the differentiation of human induced pluripotent stem cell‐derived macrophages (IPSDM) and their applications in understanding human macrophage physiology and relevant diseases. The protocol uses an embryoid body–based approach with a combination of serum‐free condition for hematopoiesis specification, followed by adherent culture with serum and M‐CSF for myeloid expansion and macrophage maturation. The protocol produced an almost pure culture of CD45 + /CD18 + macrophages yielding up to 2 × 10 7 cells per 6‐well plate of iPSCs within 24 days, demonstrating high efficiency, purity, and scalability. The IPSDM and monocyte‐derived macrophages (HMDM) cultured in the same medium were compared at morphological, functional and transcriptomic levels by RNA‐sequencing. IPSDM and HMDM showed broadly similar profiles of coding transcriptome, alternative splicing events, and long noncoding RNAs, with advantages and successful applications in disease modeling using patients‐derived and CRISPR‐edited iPSC lines. © 2018 by John Wiley & Sons, Inc.